2020
DOI: 10.1186/s12879-020-05328-5
|View full text |Cite
|
Sign up to set email alerts
|

Herpetic esophagitis in immunocompentent host: cases report

Abstract: Background: Herpetic esophagitis (EH) usually affects those who are immunocompromised and is uncommon in immunocompetent patients. In these cases, EH may occasionally present as an acute and self-limited illness. Such cases are rare and only a few have beenreported and limited published reviews exist making the benefits of antiviral therapy in immunocompetent patients unknown. Case presentation: We report four cases of young patients who presented dysphagia, odynophagia and epigastric pain. Endoscopic findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Indeed, several research groups, including our own, have shown that HSV-1 can reach, infect, and persist in the neurons of the enteric nervous system (ENS) in rodents ( Gesser and Koo, 1996 ; Brun et al., 2010 ; Hill et al., 2012 ; Brun et al., 2018 ). In humans, HSV-1 is one of the most important causes of esophagitis in immunocompromised and immunocompetent hosts ( McDonald et al., 1985 ; Mosimann et al., 1994 ; Rodrigues et al., 2004 ; Bando et al., 2009 ; Canalejo et al., 2010 ; Diezma-Martín et al., 2020 ). Even if it is not possible to discriminate between reactivation and primary infections, during the past decade, evidence has suggested that the enteric nervous system can be a primary site of reactivation of neurotropic Herpes viruses ( Gesser and Koo, 1997 ; Gilden et al., 2001 ; Chen et al., 2011 ; Gershon et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several research groups, including our own, have shown that HSV-1 can reach, infect, and persist in the neurons of the enteric nervous system (ENS) in rodents ( Gesser and Koo, 1996 ; Brun et al., 2010 ; Hill et al., 2012 ; Brun et al., 2018 ). In humans, HSV-1 is one of the most important causes of esophagitis in immunocompromised and immunocompetent hosts ( McDonald et al., 1985 ; Mosimann et al., 1994 ; Rodrigues et al., 2004 ; Bando et al., 2009 ; Canalejo et al., 2010 ; Diezma-Martín et al., 2020 ). Even if it is not possible to discriminate between reactivation and primary infections, during the past decade, evidence has suggested that the enteric nervous system can be a primary site of reactivation of neurotropic Herpes viruses ( Gesser and Koo, 1997 ; Gilden et al., 2001 ; Chen et al., 2011 ; Gershon et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many cases of isolated H. pylori infections or HSV esophagitis, but the coexistence of both H. pylori and HSV is much rarer. Few cases were identified, one in which an immunocompetent adolescent had positive serology IgM and IgG for both HSV 1 and 2, with active esophageal ulcers and gastric inflammation consistent with H. pylori gastritis [ 8 ]. This case, however, presented with fever, odynophagia, and chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms are odynophagia, dysphagia, heartburn, epigastric pain, or chest pain. Concurrent oropharyngeal lesions are uncommon in immunocompetent hosts, but immunocompromised hosts usually have co-existent herpes labialis or oropharyngeal ulcers [ 1 , 8 , 9 ]. In our case, an immunocompetent male presented with generalized body aches, epigastric pain, nausea, vomiting, and odynophagia with no fever before or during hospitalization.…”
Section: Discussionmentioning
confidence: 99%